Mapping Digital Conversation Networks of Collector Communities on Platform X: A Study of Blind Box Product Information Diffusion - Nanda Herliana; Eka Surachman; Asep Miftahuddin (CV. Media Digital Publikasi Indonesia, 2026)
The blind box phenomenon has created a complex digital conversation ecosystem on Platform X (formerly Twitter), where collector communities exchange information, unboxing experiences, and social validation. This study maps the digital conversation network structure of blind box collector communities on Platform X and traces product information diffusion patterns within it. Data were collected via the SocialX platform using the keywords “blind box” AND (“collector” OR “collection” OR “unboxing” OR “trading”), yielding 995 tweets from 716 unique accounts (January 15 to June 14, 2026), predominantly in English (77.8%) and Indonesian (11.3%). Five analytical methods were integrated: Social Network Analysis (SNA), Dynamic Network Analysis, Trend Analysis, Sentiment Analysis, and Text Network Analysis. The findings reveal a highly fragmented mention network divided into numerous small isolated clusters with content-resharing accounts (such as @youtube) and niche marketplace accounts (such as @chimpershq) emerging as the two dominant hubs. Dynamic network analysis confirmed that both hubs persisted consistently over time, indicating centralized information diffusion concentrated among a small number of actors. Trend analysis identified 11 conversation spikes concentrated in January to February 2026, followed by a significant decline in March to April, before recovering in June 2026. Sentiment analysis showed that community conversations were dominated by positive sentiment (42.71%), followed by neutral (37.59%) and negative (19.70%). Text network analysis revealed that unboxing, collection, series, and secret were the central concepts organizing community discourse. These findings contribute empirically to understanding how niche collector communities form and disseminate information on social media, while offering practical implications for digital marketing strategies targeting collectible product communities.